Redefining cancer of unknown primary: Is precision medicine really shifting the paradigm?. (June 2021) - Olivier, Timothée; Fernandez, Eugenio; Labidi-Galy, Intidhar; Dietrich, Pierre-Yves; Rodriguez-Bravo, Veronica; Baciarello, Giulia; Fizazi, Karim; Patrikidou, Anna
Highlights: Cancers of unknown primary (CUPs) account for 2 to 5% of new cancers. Biology of CUP has 2 main hypotheses, chromosomal instability is a hallmark of CUP. Almost no improvement has been seen since decades in the poor prognosis group (~85%). Precision oncology has yet failed to globally improve outcomes. New approaches are awaited and needed to improve outcomes of CUP patients. Abstract: The concept of Cancer of Unknown Primary (CUP) has evolved with the advent of medical oncology. CUP can be difficult to diagnose and represents 2 to 5% of new cancers, therefore not exceptionally rare. Within CUPs can be identified a subset of favourable prognosis tumours, however the vast majority of CUP patients belongs to a poor prognosis group. CUP features significant oncological challenges, such as unravelling biological and transversal issues, and most importantly, improving patient's outcomes. In that regard, CUP patients' outcomes regrettably showed minimal improvement for decades and CUP remains a cancer group of very poor prognosis. The biology of CUP has two main hypotheses. One is that CUP is a subgroup of a given primary cancer, where the primary is present but cannot be seen due to its small size. The other, the "true" CUP hypothesis, states that CUP share features that make them a specific entity, whatever their tissue of origin. A true biological signature has not yet been described, but chromosomal instability is a hallmark of poor prognosis CUP group. Precision oncology, despite achieving identifying the putative origin of the CUP, so far failed to globally improve outcomes of patients. Targeting molecular pathways based on molecular analysis in CUP management is under investigation. Immunotherapy has not shown ground-breaking results, to date. Accrual is also a crucial issue in CUP trials. Herein we review CUP history, biological features and remaining questions in CUP biology, the two main approaches of molecular oncology in CUP management, in order to draw perspectives in the enormous challenge of improving CUP patient outcomes.